Meningkatkan Potensi Pasar dalam Mencapai Keberhasilan UMKM Telur Puyuh di Jorong Sawah Tarok Nagari Padang Laweh Selatan - Dewi, Ika Parma; Yovi, Arsil; Fitriani, Desi; Dona, Fikhrenia Rima; Putri, Monica; Agustia, Putri Lestari; Rahma, Rahma (J-CoSE: Journal of Community Service & Empowerment, 2024)
This article we made has the issue of Increasing Market Potential in Achieving the Success of Quail Egg MSMEs in Jorong Sawah Tarok Nagari Padang Laweh Selatan. The mother who owns the cattle is named Asnimar's mother. The purpose of this activity is to increase foreign exchange between quail egg breeders and traders. The method used is the purposive method. The purposive method means that the research location was chosen deliberately based on certain objectives that are considered in accordance with the research objectives. The results of the activities contained in our article are by helping to market Hakim's quail eggs through social media such as Facebook and others